Application of Decision Support in Performance Assessment of Delivery Services in the E-Commerce Industry - Kraugusteeliana, Kraugusteeliana; Violin, Vivid (Jurnal Galaksi, 2024)
The e-commerce industry is experiencing rapid growth along with increasing consumer demand for fast, precise and reliable delivery services. Assessing the performance of goods delivery services is very important to ensure customer satisfaction and operational efficiency. This research aims to develop a decision support model to assess the performance of goods delivery services in the e-commerce industry using the Analytical Hierarchy Process (AHP) method. The AHP method was chosen because of its ability to resolve conflicting criteria through a pairwise comparison matrix and decompose problems, criteria and alternatives into a decision hierarchy. In this research there are 5 assessment criteria, namely Price (C1), Goods Packaging (C2), Goods Delivery C3), Service (C4), and Number of Branches (C5). Source of data from respondents obtained using questionnaire techniques. The research results show the final ranking of 4 alternative delivery services. From these results it can be explained that the highest criteria weight value in criterion C1 can influence the ranking results, because the AHP method is a criteria weighting method that takes into account criteria through a pairwise comparison matrix.